Stereotype threat to teacher academic performance in Huaulu, North Seram Island: the role of self-efficacy and ethnic identity - Tria Ina Utari (UIN Sunan Gunung Djati Bandung, 2022)
Understanding the positives and negatives of teachers' academic performance is an important step in improving academic success in these minority groups. Teachers are faced with a challenge stemming from the experience of ethnic groups, and customary law, in supporting their academic performance. Quantitative design is used through the distribution of questionnaires and direct observation to test whether the threat of stereotypes affects the academic performance of teachers in Huaulu and whether there is a direct influence of ethnic identity and self-efficacy on teacher academic performance. This analysis uses multiple regression and ANOVA to test the sampling method. The results showed that the threat of stereotypes affects teachers in Huaulu and there is a direct influence of the effect of ethnic identity and self-efficacy on teachers' academic performance. Originality in this study as far as the authors are aware, is the first study to dismantle the threat of teacher stereotypes in the hinterlands of the Huaulu ethnicity, little is known as to whether ethnic identity and teacher efficacy affect academic performance against the threat